Advanced lung adenocarcinoma detected by choroidal metastasis in a patient with amyopathic dermatomyositis: A case report - Takako Kawaguchi; Kei Yamasaki; Tatsuya Shingu; Taiki Manabe; Satoko Koga; Sho Naruse; Moe Kidogawa; Fuki Ujimiya; Chinatsu Nishida; Kazuhiro Yatera (Thoracic Cancer, 2022)
Abstract A 63‐year‐old Japanese man with amyopathic dermatomyositis treated with immunosuppressants became aware of distortion of his left visual field, and a metastatic choroidal tumor was suspected. His chest computed tomography (CT) showed a pulmonary nodule in the right upper lobe and mediastinal lymphadenopathy, and he was diagnosed with advanced lung adenocarcinoma with choroidal metastasis. Malignancies associated with dermatomyositis (DM) are often rapidly progressive and, in choroidal metastasis associated with lung cancer, a choroidal lesion is often diagnosed prior to lung cancer; therefore, CT performed at the time of diagnosis of choroidal metastasis may show lung cancer lesions. When ocular symptoms are observed in DM patients, metastatic malignancies should be suspected, and systemic examinations, such as positron emission tomography (PET)‐CT, should also be performed.